Optimizing Tourism Development Through Landslide Hazard Mapping in Raung Volcano - Bachri, Syamsul; Shrestha, Rajendra Prasad; Sumarmi, Sumarmi; Aksa, Furqan Ishak; Prastiwi, Mellinia Regina; Putri, Nanda Regita; Billah, Egi Nursari; Hakiki, A.Riyan Rahman; Hidiyah, Tabita May (JURNAL GEOGRAFI, 2024)
The series of volcanic activities of Mount Raung triggered primary and secondary hazards in the area around the volcano. Kalibaru watershed is one of the areas prone to landslides due to secondary hazards of eruption activity in the direction of west and northwest part of this region. This study aims to optimize tourism by mapping landslide hazard using Spatial Multi-Criteria Evaluation (SMCE) around Mount Raung. This research used 46 points of landslide data through remote sensing, field observation. Ten landslide triggering factors, namely TPI (Topographic Position Index), TWI (Topographic Wetness Index), SPI (Stream Power Index), slope, distance to river, rainfall, geology, land use, distance to road, and soil type was used to map the landslide hazard. This study used ROC (Receiver Operating Characteristic) analysis to validate the landslide susceptibility mapping with an AUC (Area Under Curve) value of 0.93, which indicates that the mapping has a high accuracy value. The results showed that the landslide susceptibility is divided into three classes: high susceptible, moderate susceptible, and low susceptible. The high susceptible area covers 151.62 km2 (21%), the moderate susceptible area covers 407.99 km2 (56%), and the low susceptible area covers 166.79 km2 (23%). Based on the results of the mapping, tourism development in the area of Mount Raung is recommended in areas that are classified as medium and low landslide susceptibility.Keywords: Mount Raung, Landslides, SMCE, Tourism Development